The impact of vorticity waves on the shock dynamics in core-collapse supernovae. Issue 3 (4th January 2018) - Huete, César; Abdikamalov, Ernazar; Radice, David
Abstract: Convective perturbations arising from nuclear shell burning can play an important role in propelling neutrino-driven core-collapse supernova explosions. In this work, we analyse the impact of vorticity waves on the shock dynamics, and subsequently on the post-shock flow, using the solution of the linear hydrodynamics equations. As a result of the interaction with the shock wave, vorticity waves increase their kinetic energy, and a new set of entropic and acoustic waves is deposited in the post-shock region. These perturbations interact with the neutrino-driven turbulent convection that develops in that region. Although both vorticity and acoustic waves inject non-radial motion into the gain region, the contribution of the acoustic waves is found to be negligibly small in comparison to that of the vorticity waves. On the other hand, entropy waves become buoyant and trigger more convection. Using the concept of critical neutrino luminosity, we assess the impact of these modes on the explosion conditions. While the direct injection of non-radial motion reduces the critical neutrino luminosity by ∼ 12 per cent for typical problem parameters, the buoyancy-driven convection triggered by entropy waves reduces the critical luminosity by ∼ 17–24 per cent, which approximately agrees with the results of three-dimensional neutrino-hydrodynamics simulations. Finally, we discuss the limits of validity of the assumptions employed.